Dead Reckoning : Memories of the 1971 Bangladesh War - Bose, Sarmila (GHQ, Rawalpindi Services Book Club, 2012)
"The 1971 Bangladesh war mired Pakistan in a brutal struggle within its own borders and against neighboring India. Backed by the Soviet Union and the United States, the players in the conflict fought over the territories of East Pakistan, which then seceded to become Bangladesh.
Include Bibliography, Notes and Index
Keywords: War and society -- Social aspects